2003
DOI: 10.1038/nbt776
|View full text |Cite
|
Sign up to set email alerts
|

Lipopeptide detergents designed for the structural study of membrane proteins

Abstract: The structural study of membrane proteins requires detergents that can effectively mimic lipid bilayers, and the choice of detergent is often a compromise between detergents that promote protein stability and detergents that form small micelles. We describe lipopeptide detergents (LPDs), a new class of amphiphile consisting of a peptide scaffold that supports two alkyl chains, one anchored to each end of an alpha-helix. The goal was to design a molecule that could self-assemble into a cylindrical micelle with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
141
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(149 citation statements)
references
References 39 publications
4
141
0
4
Order By: Relevance
“…Nevertheless, only few crystal structures of membrane proteins have been reported using peptitergents. Lipopeptides, formed by linkage of fatty acid groups to peptides, have also been described for this purpose [61]. Short heptameric peptides (consisting of seven amino acids: a hydrophilic head, aspartic acid or lysine, and a hydrophobic tail with six consecutive alanine residues) are capable of efficiently extracting membrane proteins without additional incorporation of fatty acid or other lipophilic groups and can further maintain the activity of the extracted protein [62][63][64].…”
Section: New Solubilizing Agents For Membrane Proteinsmentioning
confidence: 99%
“…Nevertheless, only few crystal structures of membrane proteins have been reported using peptitergents. Lipopeptides, formed by linkage of fatty acid groups to peptides, have also been described for this purpose [61]. Short heptameric peptides (consisting of seven amino acids: a hydrophilic head, aspartic acid or lysine, and a hydrophobic tail with six consecutive alanine residues) are capable of efficiently extracting membrane proteins without additional incorporation of fatty acid or other lipophilic groups and can further maintain the activity of the extracted protein [62][63][64].…”
Section: New Solubilizing Agents For Membrane Proteinsmentioning
confidence: 99%
“…These detergents make the protein-detergent complexes (PDC) as small as possible by creating a flat and rigid hydrophobic surface. McGregor et al have reported that lipopeptides (LPDs) are self-assembled into a cylindrical micelle with a width similar to that of a lipid bilayer, and further form a rigid sheath around the protein surface [55] . Zhang et al have developed cholate-based amphiphiles that project hydrophilic maltose units from one side of the steroidal skeleton, which is then further developed by the design of "tandem facial amphiphiles (TFAs)" [60,61] .…”
Section: Surfactantsmentioning
confidence: 99%
“…The de novo synthesis of detergents includes protein-based nanodiscs [49,50] , amphiphilic polymers (amphipols) [51][52][53] , peptide-based amphiphiles [54][55][56] , fluorinated detergents [53,57] and tripod detergents [58,59] . One good example is the socalled "facial amphiphile", which is a new detergent concept created by several groups.…”
Section: Surfactantsmentioning
confidence: 99%
“…Nonetheless, a structural study of γ-secretase substrates would shed considerable light on the mechanism of cleavage until structural information for the entire enzyme becomes available. It has been established that truncated substrates retain all the properties for cleavage in their TMD (19) and are well suited for structural determination in a micellar environment using nuclear magnetic resonance (NMR) techniques (20,21). A similar approach was previously used to determine the solution structure of the Aβ40 peptide (22).…”
mentioning
confidence: 99%